Development of water vapor permeability determination methodology for spray film-forming systems - M. M. Shumkova; M. V. Pomytkina; A. A. Ananian; G. Pouya; M. M. Agabalyan; E. O. Bakhrushina (Разработка и регистрация лекарственных средств, 2025)
Introduction. Spray film-forming systems (SFFSs) are dosage forms that form an in situ film when sprayed. One of the key features of SFFSs is partial vapor permeability, a special case of occlusion. Various methods assess vapor permeability by determining the occlusion factor, but disparate approaches in studies prevent harmonizing results and identifying optimal parameters.Aim. Development of a methodology for determining the vapor permeability of spray film-forming systems, measuring the occlusion factor and studying the most significant factors affecting the accuracy of determining this characteristic.Materials and methods. Determination of vapor permeability was carried out using a special setup, consisting of a cell with water and a membrane fixed over it, on which the model composition was applied. Measurement cylinders of 25 ml (Russia) or penicillin vials with a smooth neck of 10 ml (Russia), membranes for filtration and dialysis (nylon, EPM.K, LLC RME "Technofilter", Russia), dialysis bags MEMBRA-CEL® (cellulose acetate, Viskase Companies, Inc., USA) and Sartopure® PP3 (polypropylene, Sartorius Stedim Biotech, Germany) were used. As sealants to isolate airflow around the membrane Parafilm M, C-silicone ZetaPlus L Intro Kit (Zhermack, Poland, Italy), hotmelt adhesive Master Hand (Union Source Со., Ltd., China), UV-curable material "UNIREST" (LLC "StomaDent", Russia) were used. Comparative analysis of materials was carried out on a model composition containing 0.5 % (m/o) Kollicoat® MAE 100P (BASF, Germany), 3 % (m/o) Soluplus® (BASF, Germany), 2 % (m/o) Kollisolv® PEG-400 (BASF, Germany), 70 % ethyl alcohol (SOJSC "Ferein", Belarus).Results and discussion. The combination of Parafilm M and the presented sealants showed high performance. Synthetic membrane occlusion factor for the model substance varied depending on the membrane type from 9.35 ± 3.58 to 16.86 ± 6.09, reflecting low-medium degree of occlusion.Conclusion. In this study optimized techniques for determining the vapor permeability for SFFS were developed. It was observed that rationalized membrane selection, consideration of the probability of moisture absorption by the membranes, method of sealing and cell calibrations, temperature and humidity levels, and vapor pressure were necessary.